PROJECT WORK AS ONE OF THE MEANS CREATIVE LANGUAGE TEACHING (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article reveals the essence and practical significance of design work. The goals, objectives, and advantages of the method are given. Project work is a method of developing a problem in detail, which can result in a real positive result, a final product. It is concluded that this method activates the independence, creative and mental activity of students based on practical research of this method.